2014
DOI: 10.1007/s00405-014-2910-0
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics and surrogate markers of eosinophilic chronic rhinosinusitis in Southern China

Abstract: The surrogate markers for subclassifying eosinophilic chronic rhinosinusitis (ECRS) and non-ECRS remain elusive. We herein performed a cross-sectional study to assess the clinical implication of clinical symptoms, CT findings, blood eosinophil (EOS) examination based on histological examination of tissue eosinophilia in 105 adult CRS patients (including 72 with nasal polyps and 33 without nasal polyps) in southern China. We found the mean score of smell loss was significantly higher in ECRS subgroup than those… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
32
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(37 citation statements)
references
References 20 publications
4
32
1
Order By: Relevance
“…According to prior studies, tissue eosinophilia is correlated with olfactory dysfunction in CRS. 8, 10, 31 Other studies concluded that there is a relationship between tissue eosinophilia and worse disease severity as defined by preoperative CT and endoscopy scores; however, these study cohorts included both CRSsNP and CRSwNP patients and the analyses were not always stratified by subtype. 10, 11 We note that in these studies Kountakis et al 11 did not specify the exact biopsy location and Soler et al 10 evaluated eosinophilia in ethmoid mucosa.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to prior studies, tissue eosinophilia is correlated with olfactory dysfunction in CRS. 8, 10, 31 Other studies concluded that there is a relationship between tissue eosinophilia and worse disease severity as defined by preoperative CT and endoscopy scores; however, these study cohorts included both CRSsNP and CRSwNP patients and the analyses were not always stratified by subtype. 10, 11 We note that in these studies Kountakis et al 11 did not specify the exact biopsy location and Soler et al 10 evaluated eosinophilia in ethmoid mucosa.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies have investigated the relationship between eosinophilic inflammation and comorbid asthma, but the histopathologic definitions of eosinophilia used in these studies are quite variable. 11, 17, 20, 31 Zuo et al 31 and Kountakis et al 11 both reported an increased frequency of asthma in CRS patients with higher eosinophil densities ( > 5 eosinophils/high-power field [HPF]) in sinus mucosal or NP tissue. Similarly, Tokunaga et al 20 found that asthma was more prevalent in CRS patients with higher eosinophil densities ( > 70 eosinophils/HPF) in NP or polypoid tissue from the ethmoid cavity.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, these reduced functions of NK cells correlate inversely with blood eosinophil counts12. Peripheral blood eosinophilia is well known to be related to tissue eosinophilia and recurrence of CRS after surgery131415. These findings suggest that the immune regulatory function of NK cells may play a role in regulating the eosinophilic inflammation in CRS.…”
mentioning
confidence: 96%
“…Ouyang et al 35 (n=86) found smell loss and cough to be associated with eCRS on a modified SNOT questionnaire. Both Zuo et al 36 (n=105) and Haruna et al 37 (n=84) also found eCRS to be significantly associated with smell loss utilizing a 7-point VAS scale and 10-point VAS scale, respectively. Together, these studies suggest that mucosal eosinophilia is strongly associated with smell loss.…”
Section: Discussionmentioning
confidence: 89%